The Effect of Debt Default, Profitability, and Financial Distress on Going Concern Audit Opinion Acceptance - Rohmawati, Siti Aminah; Djamhuri, Ali (Future Science, 2024)
This study aims to analyze the effect of debt default, profitability, and financial distress on going concern audit opinion. The objectt of this research includes the manufacturing company listed on the Indonesia Stock Exchange in 2019 -2022. Independent variables in this research are debt default, profitability. The dependent variabel in this research is going concern audit opinion. This study utilizes samples of 248 secondary data of audited financial reports obtained from 62 manufacturing companies in 2019 – 2022 according to predetermined criteria, selected through purposive sampling. The debt default and profitability are measured by the Current Ratio and Return on Assets ratio, respectively, and financial distress is represented by the Altman Z-score model. The results of the logistic regression analysis exhibit that debt default and financial distress have a significant effect on going concern audit opinion while profitability has no effect on going concern audit opinion.